Mechanical characterization of the human pia-arachnoid complex. (August 2021) - Benko, Nikolaus; Luke, Emma; Alsanea, Yousef; Coats, Brittany
Abstract: Traumatic brain injury (TBI) is a significant problem in global health that affects a wide variety of patients. Mild forms of TBI, commonly referred to as concussion, are a result of rapid accelerations of the head from either direct or indirect impacts. Kinetic energy from the impact is transferred into deformation of the brain, leading to cellular disruption. This transfer of energy is in part mediated by the pia-arachnoid complex (PAC), a layer of anatomical structures that forms the physical connection between the brain and the skull. The importance of properly quantifying the mechanics of the PAC for use in computational models of TBI has been understood for some time, but data from human subjects has been unavailable. In this study, we quantify the normal traction modulus of the PAC in five post-mortem human subjects using hydrostatic fluid pressurization in combination with optical coherence tomography. Testing at multiple locations across each brain reveals that brain-skull stiffness is heterogeneously distributed. The material response to traction loading was linear, with a mean normal traction modulus of 12.6 ± 4.8 kPa. Modulus was 21% greater in superior regions of the brain compared to inferior regions. Comparisons with regional microstructural data suggests a potential relationship between the volume fraction of arachnoid trabeculae and modulus. Comparisons to coincident measurements of microstructural properties showed a positive correlation between arachnoid membrane thickness and normal traction modulus. This study is the first to characterize the mechanics of the human pia-arachnoid complex and quantify material properties in situ. These findings suggest implementing a heterogeneous model of the brain-skull interface in computational models of TBI may lead to more realistic injury prediction.